Quasi-Linear Algebras and Integrability (the Heisenberg Picture) - Vinet, L.; Zhedanov, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We study Poisson and operator algebras with the ''quasi-linear property'' from the Heisenberg picture point of view. This means that there exists a set of one-parameter groups yielding an explicit expression of dynamical variables (operators) as functions of ''time'' t. We show that many algebras with nonlinear commutation relations such as the Askey-Wilson, q-Dolan-Grady and others satisfy this property. This provides one more (explicit Heisenberg evolution) interpretation of the corresponding integrable systems.